Planktic foraminiferal response to an early Paleocene transient warming event and biostratigraphic implications - Bornemann, André; Jehle, Sofie; Lägel, Friederike; Deprez, Arne; Petrizzo, Maria Rose; Speijer, Robert P. (International Journal of Earth Sciences, 2021)
The Latest Danian Event (LDE, ~ 62.2 Ma) is characterized by global changes in the carbon cycle as indicated by two nega-tive δ13C excursions of up to ~ 1‰. These δ13C shifts are accompanied by a 2–3 °C warming of both surface and deep waters based on benthic and planktic foraminiferal δ18O measurements, and the LDE has, thus, been considered as a so-called hyperthermal event. The event lasted for 200 kyr and has been identified in various ocean basins and shallow marine settings. Here, we present a compilation of data from three deep-sea cores covering the Pacific, North and South Atlantic oceans as well as a southern Tethyan shelf section to document the response of planktic foraminifera assemblages to ocean warming. In all studied successions, we observe the disappearance of the planktic foraminifer genus Praemurica on a global scale that took place close to the onset of the LDE. Moreover, on the long run, praemuricids were contemporaneously replaced by morozovellids. Both the decline of Praemurica and a temperature increase started between 200 and 260 kyr before the LDE onset and were punctuated by the LDE itself. In this paper, we propose two mechanisms that have controlled the envi-ronmental changes associated with this event, (1) increased activity of the North Atlantic Igneous Province acting on long time-scales, and (2) changes of orbital parameters resulting in insolation changes on shorter time-scales.In contrast to a proposed muted benthic foraminiferal response, the planktic community has been substantially impacted by the LDE as indicated by changes in planktic foraminifera faunas and calcareous nannofossils. Finally, our quantitative and conventional approaches identifying stratigraphically important planktic foraminifera datum levels justify a revision of the upper Danian to lower Selandian planktic foraminifera biozonation.